Qoheleth : the ironic wink - Crenshaw, James L. (Columbia, SC : University of South Carolina Press, 2013)
Rarely does a biblical book evoke admiration from a Nobel laureate in literature, a newspaper columnist, a prize-winning poet, and a popular songwriter. Ecclesiastes has done that, and for good reason. Its author, who called himself Qoheleth, stared death in the face and judged all human endeavors to be futile. For Qoheleth observation is the only avenue to understanding; an arbitrarily wrathful and benevolent deity created and rules over the world; and death is unpredictable, absolute, and final. His message is simple: seize the moment, for death awaits. James L. Crenshaw begins by examining the essential mysteries of the book of Ecclesiastes: the speaker's identity, his emphasis on hidden or contradictory truths, and his argument of the insubstantiality of most things and the ultimate futility of all efforts. Moving from the ancient to the contemporary, Crenshaw again analyzes Qoheleth's observations about the human condition, this time testing if they can stand up against rational inquiry today. In exploring Qoheleth's identity, the foundations of his outlook, and his recommendations, Crenshaw engages modern readers in a conversation about one of the most disagreed upon biblical books. In Qoheleth, Crenshaw draws on related literature from the ancient Near East and traces the impact of Qoheleth in both Christian and Jewish traditions, summarizing a lifetime of scholarship on the book of Ecclesiastes. While exploring Ecclesiastes and its enigmatic author, Crenshaw engages scholars and modern interpreters in genuine debate over the lasting relevance of Qoheleth's teachings and the place of Ecclesiastes in the biblical canon.
Authorial deceit -- Veiled truth? -- Elusive essence -- Ocular deception -- Surreptitious givens -- Victorious time -- Tasty nectar -- Flawed genius.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Bible. -- Criticism, interpretation, etc; Bible; RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Biblical Studies -- Wisdom Literature; RELIGION / Biblical Biography / Old Testament; Electronic books; Criticism, interpretation, etc